The financing of forest carbon projects: Existing experiences and opportunities in Mexico - Ranero, Alejandro; Covaleda, Sara (Instituto de Ecología, A.C., 2018)
This paper presents a synthesis of the financing mechanisms used internationally for the mitigation of greenhouse gas emissions in the forestry sector, and the experiences developed in Mexico. In addition, the mitigation opportunities of the Land Use, Land Use Change and Forestry sector [Lulucf] to meet national goals are analyzed. At the international level, forest carbon projects have participated in voluntary and compliance market schemes although forest projects from developing countries have had a limited role under the Kyoto Protocol. The development of new mitigation mechanisms under the United Nations Framework Convention on Climate Change [Unfccc] implied the need to expand the financing approaches, and the bilateral and multilateral agreements for the Reduction of Emissions from Deforestation and Forest Degradation plus conservation, increase of carbon stocks and sustainable forest management [REDD+] mechanism in different countries, are examples of that. In Mexico, the participation of the forestry sector in the voluntary carbon market and the Clean Development Mechanism has been limited. However, the country engaged in the preparation of a REDD+ mechanism at the national level, and is implementing its Emissions Reduction Initiative [ERI]. To achieve emissions reduction goals in the Lulucf sector, Mexico must achieve an effective coordination between forestry and climate change policies and an optimal use of the financial mechanisms that are being developed, specially the ERI’s experience and the development of an Emission Trading Scheme at the national level. In this regard, the acceptance of offset credits from different types of forestry projects, in a broader perspective than that contemplated for the optional payment of the carbon tax through carbon credits, could result in important environmental, economic and social benefits.